Innovations in the practice of Brazilian community health nursing during the pandemic: a rapid review. - Santos Zanchetta, Margareth; Moura de Paula, Clarissa; Lima Moraes, Katarinne; Silva Santos, Walterlânia; Pereira Linhares, Francisca Márcia; de Almeida Cavalcante Oliveira, Lizete Malagoni; Visconde Brasil, Virginia; de Fatima Silva Viduedo, Alecssandra (Anna Nery School Journal of Nursing / Escola Anna Nery Revista de Enfermagem, 2024)
Objective: to describe the innovations introduced in Brazilian community health nursing during the COVID-19 pandemic. Method: rapid literature review with a conceptual framework of innovation in organizations and ideas underlying the method of appreciative inquiry. The databases were limited to Google Scholar (English) and SciELO (Portuguese) (November–December 2022). A total of 52 articles were identified in Portuguese, 11 of which met the eligibility criteria. Results: the majority (n=10; 91%) addressed the “discovery” factor, highlighting the favorable conditions for innovation. Contents about “imagining what could be” (n=6; 55%) projected innovation as a permanent practice. In relation to “co-constructing the ideal condition” 55% (n=6), innovation was reported as a joint action and in practice. Regarding the “sustainability of innovation,” only five interventions (45%) indicated paths for continuity. Conclusions and implication to the practice: the connection between primary health care, academia, and organizations produced simple solutions to unknown, complex, and unpredictable situations. However, the idea of innovation as something unprecedented, untested, and structurally revolutionary, was not extensively identified by this rapid review, due to the conceptual and theoretical fragility of the interventions and projects reported.